Process and Impact of Globalization in Nepalese Women - Sharma, Manju (Dhaulagiri Journal of Sociology and Anthropology, 2015)
This paper explores the impact of globalization in Nepalese women. The changes on the women’s way of life due to globalization can be seen directly in the economy, media, IT sectors, various parts of society and ultimately in the culture. When the Nepalese women entered into the globalization process the Hindu norms and values of the society (where more than 82 percent are Hindu) has creolized with the global way of life. The women are becoming more self- reliant and empowered due to globalization but at the same time they are entering more risky markets to fulfill the desires that floated by the globalization. Similarly, globalization has offered various employment opportunities and exposure in international arena, but it also creates mental anxiety, depression and sexual abuse for those remaining in or outside the country. As there is very limited research and study on the impact of globalization in the Nepalese society, it is too early to conclude the impact of globalization as good or bad on Nepalese women.